Perfil dos interessados no cursinho metamorfose do IBILCE - Rodrigues, Joseane Gabriel [UNESP]; Alvares, Jackson Americo [UNESP]; Abrahão, Thiago Henrique de Camargo [UNESP]; Cruz, Luciana Aparecida Nogueira da [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The free college preparatory courses have been the alternative for people who want to pursue higher education and have no knowledge to be selected in the entrance examination of universities and have no financial means to bear the costs of a college preparatory course or private college. Among the projects of University of São Paulo State - UNESP, the Project Preparatory Courses deserves attention. In 22 campuses of UNESP, vacancies are offered to the population that wants to join in higher education and need to attend a preparatory course. The Metamorfose’s College Preparatory Course is one of the UNESP’s free college preparatory courses, and offers 100 vacancies annually. We have analyzed the backgrounds of the candidates who applied in selection processes in the years of 2011, 2012 and 2013. The data in the application forms indicate that most of the candidates are female, coming from public primary and secondary education, with low family income (up to R $ 1,300.00). The university course that most candidates want to join is the medical school.

Os cursinhos pré-vestibulares comunitários gratuitos têm sido a alternativa para pessoas que pretendem cursar o ensino superior e não têm conhecimento necessário para serem selecionados nos exames vestibulares das Universidades e não têm condições financeiras para arcar com os custos de um cursinho ou faculdade particular. Dentre os projetos de Extensão Universitária da Universidade Estadual Paulista – UNESP, o Projeto Cursinhos Pré-Vestibular merece destaque. Em 22 campi da UNESP, são oferecidas vagas para a população que almeja ingressar no ensino superior e precisa frequentar um cursinho. O Cursinho Metamorfose é um dos cursinhos da UNESP e oferece anualmente 100 vagas. Analisamos o perfil dos candidatos que se inscreveram nos processos seletivos nos anos de 2011, 2012 e 2013. Os dados obtidos nas fichas de inscrição indicam que a maioria dos candidatos é do sexo feminino, oriunda dos ensinos fundamental e médio públicos, com renda familiar baixa (até R$1.300,00). O curso superior que a maioria dos candidatos pretende ingressar é o de medicina.
Keywords: College preparatory course; University extension; Volunteering; Cursinho pré-vestibular; Extensão universitária; Voluntariado